INTERACTIONS AMONG INSIDER OWNERSHIP, DIVIDEND POLICY, DEBT POLICY, INVESTMENT DECISION, AND BUSINESS RISK - Indri Erkaningrum F. (Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
The study of interaction among insider ownership, dividend policy, debt policy, investment decision, and business risk is still conducted. This research aims at investigating the influencing factors of insider ownership, dividend policy, debt policy, investment decision, business risk, and the interaction among insider ownership, dividend policy, debt policy, investment decision, and business risk. The samples of the research are 137 manufacturing companies listed in the Indonesia Stock Exchange from the year 2006 to 2010. The three stages least square simultaneous equation model is used to analyze the interaction among insider ownership, dividend policy, debt policy, investment decision, and business risk. The analysis result of insider ownership equation shows that investment, business risk, and size have negative influence on insider ownership. Insider ownership, debt and business risk give negative impact to dividend that is shown on equation of dividend. Negative impact of dividend, business risk, and profitability to debt is shown on equation of debt. The analysis result of investment equation shows that insider ownership and business risk have negative influence on investment, whereas profitability and sales growth have positive influence on investment. The analysis result of business risk equation shows that insider ownership, dividend, investment, and size have negative influence on business risk, whereas variability of earnings has positive influence on business risk. The analysis result of the interaction among insider ownership, dividend policy, debt policy, investment decision, and business risk shows that: 1) there are reciprocal interactions among insider ownership, investment, and business risk; 2) there are reciprocal interactions between dividend and debt; 3) there are reciprocal interactions between dividend and business risk; 4) insider ownership influences dividend; 5) business risk influences debt. The empirical evidence of interaction among insider ownership, dividend policy, debt policy, investment decision, and business risk helps the companies to make financial policy minimize agency problem.